2015
DOI: 10.1155/2015/680308
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment after Severe Traumatic Brain Injury, Clinical Course and Impact on Outcome: A Swedish-Icelandic Study

Abstract: Objective. To assess the clinical course of cognitive and emotional impairments in patients with severe TBI (sTBI) from 3 weeks to 1 year after trauma and to study associations with outcomes at 1 year. Methods. Prospective, multicenter, observational study of sTBI in Sweden and Iceland. Patients aged 18–65 years with acute Glasgow Coma Scale 3–8 were assessed with the Barrow Neurological Institute Screen for Higher Cerebral Functions (BNIS) and the Hospital Anxiety and Depression Scale (HADS). Outcome measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 37 publications
6
25
0
3
Order By: Relevance
“…BNIS has documented validity (34)(35)(36), is easily applicable in clinical routine and has been used in some studies of TBI (36)(37)(38) as well as stroke (39,40). A recent study of patients with severe TBI with BNIS reported that most improvement occurred during the first three months after the injury while cognition was fairly stable between 3 and 12 months (41).…”
Section: Introductionmentioning
confidence: 99%
“…BNIS has documented validity (34)(35)(36), is easily applicable in clinical routine and has been used in some studies of TBI (36)(37)(38) as well as stroke (39,40). A recent study of patients with severe TBI with BNIS reported that most improvement occurred during the first three months after the injury while cognition was fairly stable between 3 and 12 months (41).…”
Section: Introductionmentioning
confidence: 99%
“…18 Most studies have focused on deficits in memory, processing speed, visual spatial abilities, concentration, learning abilities, and abstract reasoning. 19 There is an emerging interest in evaluating the impact of these cognitive disorders on the patient's life using self-rated HRQoL (Health Related Quality of Life) tool after TBI 20 and the importance of early screening of cognitive function for rehabilitation planning in a clinical setting at a stage were the neuroplasticity is at its maximum. 21 Many standardised neurocognitive tests have been developed in the western countries.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Study design has been described previously. 16,17 In brief, inclusion criteria were severe, non-penetrating, traumatic brain injury requiring neurointensive care, with acute Glasgow Coma Scale score of [3][4][5][6][7][8]19 in adult patients aged 18-65 years.…”
Section: Methodsmentioning
confidence: 99%